2016
DOI: 10.1016/j.apsb.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of gallocatechin-7-gallate from Pithecellobium clypearia Benth. in rats

Abstract: The pharmacokinetic profile of gallocatechin-7-gallate (J10688) was studied in rats after intravenous administration. Male and female Sprague-Dawley (SD) rats received 1, 3, and 10 mg/kg (i.v.) of J10688 and plasma drug concentrations were determined by a high performance liquid chromatography-mass spectrometry (LC–MS) method. The pharmacokinetic software Data Analysis System (Version 3.0) was used to calculate the pharmacokinetic parameters. For different i.v. doses of J10688, the mean peak plasma concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…As a novel host cdc2-like kinase 1 inhibitor, gallocatechin-7-gallate which was isolated from P . clypearia ( Li et al, 2016 ) exhibited potent in vivo and in vitro activities against influenza virus ( Li et al, 2018 ). For instance, gallocatechin-7-gallate could significantly improve the survival rate of the mice that were infected with H1N1 virus and reduce the lung virus titer, indicating a promising drug candidate for antiviral therapy ( Li et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a novel host cdc2-like kinase 1 inhibitor, gallocatechin-7-gallate which was isolated from P . clypearia ( Li et al, 2016 ) exhibited potent in vivo and in vitro activities against influenza virus ( Li et al, 2018 ). For instance, gallocatechin-7-gallate could significantly improve the survival rate of the mice that were infected with H1N1 virus and reduce the lung virus titer, indicating a promising drug candidate for antiviral therapy ( Li et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the mortality rate decreased by 91.67% after J10688 treatment. Our previous study on the pharmacokinetics and tissue distribution of J10688 proved that it has a limited oral bioavailability but a wide distribution across all organs and tissues after intravenous administration, accumulating especially in lung tissues, where the influenza virus mainly occurs [12]. This drug distribution to the target organ provides the basis of the pharmacological activity of J10688 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We have also found that several chemical constituents from P. clypearia, including J10688, exhibited influenza virus neuraminidase-inhibitory activity and anti-inflammatory activity in vitro [11]. The pharmacokinetic properties of J10688 in Sprague-Dawley (SD) rats have also been studied to obtain a better understanding of its pharmacological function and mechanism [12]. In this study, the activity of J10688 was further investigated, including the anti-influenza H1N1 virus effect in vivo and the efficacy against H1N1, H3N2, and subtype B in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Pithecellobium clypearia Benth. (accepted name: Archidendron clypearia (Jack) I.C.Nielsen; Mimosaceae) is widely cultivated in the South of China, such as Guangdong, Yunnan, and Sichuan provinces, and is a prominent and clinically applied traditional Chinese medicine (Li et al, 2016). It is reported that flavonoids are the main active ingredients in P. clypearia possessing antiinflammatory and antiviral properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that flavonoids are the main active ingredients in P. clypearia possessing antiinflammatory and antiviral properties. In China, TCM doctors use Chinese traditional patent medicine obtained from the extract of aerial part of P. clypearia to treat various infections and inflammatory conditions, such as upper respiratory tract infections, laryngitis, pharyngitis, acute gastroenteritis and tonsillitis, and bacterial dysentery (Li et al, 2006;Bao et al, 2009;Li et al, 2016). However, there are no reports on the pharmacological effects and its underlying mechanisms of P. clypearia in therapeutic potential of psoriasis.…”
Section: Introductionmentioning
confidence: 99%